Relationship between Muhammadiyah and Politics in Parliament Democracy Period (A Case Study in Banyumas) - Suwarno Suwarno (Diponegoro University, 2020)
This study identifies steps taken by Muhammadiyah in the political arena during the Parliamentary Democracy period which was established through its proximity with Masyumi. Muhammadiyah was known as a special member of Masyumi at that time. This political phenomenon occurred both at national and local levels, in this case in Banyumas. The breakthrough was conducted by important figures such as K.H.A. Dardiri and S. Notosuwiryo. Muhammadiyah of Banyumas district had played an important role in establishing the Ministry of Religion of the Republic of Indonesia which was finally granted by the government. By Masyumi as its political articulation, Muhammadiyah figures in Banyumas had a lot to perform among political matters, mainly in Temporary Regional Houses Representatives of Banyumas (DPRDS) in 1950 which were quite dominant. The study used a historical approach to explore sources as evidence to strengthen the argument that Muhammadiyah and Masyumi in Banyumas had played an important role in social, economic, and community culture. It addresses the stigma that Muhammadiyah is very identical to Masyumi, if it is examined further then they have the same goal, namely a modernist movement. This step gives an affirmation that Muhammadiyah becomes a strong religious organization. Muhammadiyah embodies its goal by focusing on developing social, religious, and educational fields, while Masyumi's goal was purely in developing political parties. However, it is found that the number of human resources owned by Muhammadiyah is getting less. If the situation still occurs, then the majority of educational institutions experience teacher limitations.